Frictional heterogeneities on carbonate‐bearing normal faults: Insights from the Monte Maggio Fault, Italy. Issue 12 (2nd December 2014) - Carpenter, B. M.; Scuderi, M. M.; Collettini, C.; Marone, C.
Abstract Observations of heterogeneous and complex fault slip are often attributed to the complexity of fault structure and/or spatial heterogeneity of fault frictional behavior. Such complex slip patterns have been observed for earthquakes on normal faults throughout central Italy, where many of the Mw 6 to 7 earthquakes in the Apennines nucleate at depths where the lithology is dominated by carbonate rocks. To explore the relationship between fault structure and heterogeneous frictional properties, we studied the exhumed Monte Maggio Fault, located in the northern Apennines. We collected intact specimens of the fault zone, including the principal slip surface and hanging wall cataclasite, and performed experiments at a normal stress of 10 MPa under saturated conditions. Experiments designed to reactivate slip between the cemented principal slip surface and cataclasite show a 3 MPa stress drop as the fault surface fails, then velocity‐neutral frictional behavior and significant frictional healing. Overall, our results suggest that (1) earthquakes may readily nucleate in areas of the fault where the slip surface separates massive limestone and are likely to propagate in areas where fault gouge is in contact with the slip surface; (2) postseismic slip is more likely to occur in areas of the fault where gouge is present; and (3) high rates of frictional healing and low creep relaxation observed between solid fault surfaces could lead to significant aftershocks in areas of low stress drop.